Role of Computed Tomography in the Evaluation of Mediastinal Masses and its Correlation with Histopathological Diagnosis - K. S. Vedaraju; Pasupuleti, Jagadeesh; Khatoon, Neha; Eada, Sabarinath (Asian Journal of Medical Radiological Research, 2021)
Background: To assess the role of Computed Tomography in the Evaluation of Mediastinal Masses and its correlation with the histopathological diagnosis. Subjects and Methods: A prospective study done in the Radiodiagnosis department, Narayana medical college. The study population included 30 patients who underwent CT evaluation in our institution from January 2018 to December 2020. Patients of clinically suspected mediastinal masses with symptoms and incidentally detected mediastinal masses on chest radiograph were investigated by CT scan and subsequently proved by histopathology where possible. Results: Out of the thirty cases, the most commonly involved compartment was the anterior mediastinum (19 cases), followed by the posterior (8 cases) and middle mediastinum (3 cases). Among the 30 cases, 28 cases (94%) were predicted accurately by CT compared with histopathology. Conclusion: CT yields diagnostic information that facilitates the distinction of disease processes and tumours involving the mediastinum. In a specific clinical setting, variables such as attenuation, calcification, contrast enhancement, relationship to adjoining mediastinal structures, and related intrathoracic findings can be suggestive of a selected diagnosis.